Strategi Inovatif dalam Pembelajaran Pendidikan Agama Islam untuk Mengatasi Masalah Perilaku di Sekolah SMP Muhammadiyah 49 Medan - Dahnial, Fachri (Integrasi: Jurnal Studi Islam dan Humaniora, 2024)
This study aims to explore innovative strategies in Islamic Religious Education (Pendidikan Agama Islam/PAI) to address behavioral issues at SMP Muhammadiyah 49 Medan. The research identifies the behavioral challenges faced by students in the school, including disruptive behavior, lack of discipline, and low engagement in religious activities. Through qualitative methods, the study analyzes various teaching strategies employed by PAI teachers, focusing on those that integrate Islamic values and creative approaches to enhance student behavior. The findings highlight the effectiveness of interactive learning methods, such as role-playing, storytelling, and group discussions, in fostering positive behavior. Additionally, the study emphasizes the importance of character-building activities, such as religious counseling, community service, and motivational sessions, in shaping students' attitudes. The research concludes that implementing innovative strategies in PAI can significantly improve students' behavior, making them more disciplined and engaged in both academic and religious practices. This approach not only addresses behavioral problems but also contributes to the holistic development of students in line with Islamic principles. The study suggests that schools adopt more varied and student-centered teaching methods to promote a positive learning environment.